Comprehensive assessment of dentists knowledge and awareness about Cone Beam Computed Tomography technique used in dental implant therapies: An original research study - Kumar, Nitesh; Noorani, Syed Mohammed; Ningthoujam, Bebineeta; Govil, Himani; Julfekar; Rawat, Pratibha (International journal of health sciences, 2022)
Aim: The aim of this study was to assess the existing knowledge and awareness about Cone Beam Computed Tomography among general dental practitioner in Bhopal District, India. Materials & Methods: Total 250 private general dental practitioners of Bhopal were approached for the study. However, after considering various factors this number was reduced to 160 general dental practitioners. Questions of CBCT knowledge and awareness were prepared in a questionnaire style. It was an exclusive close ended questionnaire containing 8 questions. Questionnaire was emailed to the email addresses of the participating dentists. Informed consent was obtained from the respondents those were willingly ready for involvement. The study was conducted over a period of 1 month in which dentists are asked to fill and send back the questionnaire. P value less than 0.05 was considered significant (p< 0.05). Statistical Analysis & Results: Statistical analysis was completed by using statistical software Statistical Package for the Social Sciences version. Out of 160 practitioners, males were 109 and females were 51. Total 41 practitioners were belonging to age group >55 years. Total 120 practitioners were practicing for less than 5 years. Nevertheless, 24 practitioners were practicing in the range of 5 to 10 years.